Data science and machine learning with Python--Hands on! - Kane, Frank; Safari eBooks ([Place of publication not identified] : Packt Publications, 2016)
"The job of a data scientist ... involves analyzing large amounts of data, and gathering actionable business insights from it using a variety of tools. This course will help you take your first steps in the world of data science, and empower you to conduct data analysis and perform efficient machine learning using Python. Gain value from your data using the various data mining and data analysis techniques in Python, and develop efficient predictive models to predict future results. You will also learn how to perform large-scale machine learning on Big Data using Apache Spark."--Resource description page.
Title from resource description page (Safari, viewed January 27, 2017).
Presenter, Frank Kane.
Keywords: Data mining; Machine learning; Artificial intelligence; Python (Computer program language); Spark (Electronic resource : Apache Software Foundation); Electronic books